1995
DOI: 10.1111/j.1365-2125.1995.tb04540.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of antifungal agents on zidovudine glucuronidation by human liver microsomes.

Abstract: Zidovudine (ZDV) is extensively metabolised by the liver to an inactive glucuronide (GZDV). Since ZDV is often administered with antimycotic drugs, we studied the effect of six systemic antifungal agents on the in vitro glucuronidation of ZDV by human liver microsomes. 5-fluorocytosine and itraconazole had no inhibitory effect whereas amphotericine B, ketoconazole, miconazole and fluconazole inhibited in vitro GZDV formation (Ki values were 0.13, 0.08, 0.18 and 1.4 mm respectively).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
16
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 14 publications
2
16
0
Order By: Relevance
“…Its IC 50 value (39 mM) closely agreed with the K i value of 0.08 mM 21) for the glucuronidation of the antiviral drug, zidovudine, catalyzed by human hepatic microsomes. Grosso et al reported that ketoconazole is substituted with estrogen bound to sex steroid binding globulin present in the circulat- 1848 Vol.…”
Section: Discussionsupporting
confidence: 66%
“…Its IC 50 value (39 mM) closely agreed with the K i value of 0.08 mM 21) for the glucuronidation of the antiviral drug, zidovudine, catalyzed by human hepatic microsomes. Grosso et al reported that ketoconazole is substituted with estrogen bound to sex steroid binding globulin present in the circulat- 1848 Vol.…”
Section: Discussionsupporting
confidence: 66%
“…However, several lines of investigation described below seem to support the in vivo inhibitory effect of ketoconazole. First, the K i values of ketoconazole for the inhibition of M-3-G and M-6-G formation were close to the K i (80 M) seen for the inhibition of zidovudine glucuronidation (Sampol et al, 1995). In addition, fluconazole, another azole drug, is known to affect the bioavailability of zidovudine in vivo (Kiang et al, 2005).…”
Section: Discussionsupporting
confidence: 56%
“…If this is true, the following may be the reason codeine synergistically enhances the inhibitory effect of ketoconazole: that is, ketoconazole may bind to its specific site to modulate efficacy and/or specificity in the interaction of opioid and its association site. Ketoconazole is suggested to be a competitive inhibitor of zidovudine UGT in human liver microsomes (Sampol et al, 1995) (Table 1). Since zidovudine glucuronidation is catalyzed by UGT2B7 (Court et al, 2003), it is reasonable to consider that ketoconazole also directly inhibits UGT2B7-catalyzed zidovudine glucuronidation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations